2000
DOI: 10.1074/jbc.m003834200
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin Type 1 Repeats Interact with Matrix Metalloproteinase 2

Abstract: Thrombospondins are thought to function as inhibitors of angiogenesis. However, the mechanism(s) of this activity is not well understood. In this study, we have used the yeast two-hybrid system to identify proteins that interact with the thrombospondins 1 (TSP1) and 2 (TSP2) properdin-like type 1 repeats (TSR). One of the proteins identified that interacted with both TSR was matrix metalloproteinase 2 (MMP2). The isolated MMP2 cDNA clone encoded amino acid residues 237-633, which include the fibronectin-like g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
167
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(174 citation statements)
references
References 46 publications
4
167
0
1
Order By: Relevance
“…Thrombospondin 2 is another potent inhibitor of angiogenesis (Streit et al, 1999). This effect may be due to its ability to inhibit activation of pro-MMP9 protein, as well as downregulate MMP9 expression through a receptor-mediated event (Bein and Simons, 2000;Kamochi et al, 2003). Decreased THBS2 levels may be the result of enhanced MYB expression, which can antagonize transcription of THBS2 (Bein et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombospondin 2 is another potent inhibitor of angiogenesis (Streit et al, 1999). This effect may be due to its ability to inhibit activation of pro-MMP9 protein, as well as downregulate MMP9 expression through a receptor-mediated event (Bein and Simons, 2000;Kamochi et al, 2003). Decreased THBS2 levels may be the result of enhanced MYB expression, which can antagonize transcription of THBS2 (Bein et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting activities have also been reported, as TSP-1 upregulates MMP-9 expression and stimulates invasion of endothelial cells in vitro (Qian et al, 1997). Yeast two-hybrid assays revealed that the thrombospondin type 1 repeats in TSP-1 and TSP-2 interact with the collagen-binding domain of MMP-2 and MMP-9 indicating the potential inhibition mechanism (Bein and Simons, 2000).…”
Section: Gelatinase Inhibitors Naturally Occuring Gelatinase Inhibitorsmentioning
confidence: 99%
“…Other extra domains that are not common to all members of MMPs include the collagenbinding domain (CBD) of gelatinases and the transmembrane domains of MT-MMPs. The CBD domain is composed of three fibronectin type II like repeats and is involved in binding of collagenous substrates and elastin (Steffensen et al, 1995), fatty acids (Berton et al, 2001) and thrombospondins (Bein and Simons, 2000). Although most of the MMPs are secreted proteins, six of them contain a transmembrane domain that is used to anchor these proteins on the cell surface.…”
Section: Structural Features Of Matrix Metalloproteinasesmentioning
confidence: 99%
“…By contrast, TSP-1 is highly expressed by stromal fibroblasts, macrophages and endothelial cells in breast cancer [7]. In the tumor microenvironment, TSP-1 interacts with a wide range of other proteins to affect (1) the level of active transforming growth factor β (TGFβ) [8,9], (2) the level of vascular endothelial cell growth factor (VEGF) [10,11], (3) the composition of the extracellular matrix and the activity of extracellular proteases [10,12], and (4) the survival and migration of endothelial cells [13][14][15]. In addition, TSP-1 may inhibit tumor angiogenesis by down-regulating circulating endothelial cell progenitors [16,17].…”
Section: Introductionmentioning
confidence: 99%